UJI AKTIVITAS ANTIBAKTERI GEL EKSTRAK DAUN PETAI (Parkia SpeciosaHassk.) TERHADAP BAKTERI STAPHYLOCOCCUSAUREUS - Nafi’ah, Rahma; Haryati, Etty; Tamara, Neneng Cahya (Sekolah Tinggi Ilmu Kesehatan Holistik, 2017)
Background: Petai leaf (Parkia Speciosa Hassk) contains flavonoids and terpenoids that are suspected of having antibacterial activity. KHM values ??were tested at 2.5% extract concentration, 5.0% and 7.5%. From the results of KHM values ??obtained then developed formulations using gel base HPMC, Karbopol and Gom Arab. Objective: To find out the value of KHM from petai leaf extract (Parkia Speciosa Hassk) and gel base which has the best and stable antibacterial activity value to storage condition. Methods: This research method using a kind of experimental research. The test results were analyzed using a statistical calculation method Analysis Of variance (ANOVA) one line and then proceed with the t-test method. Result: The results showed that parkia speciosa leaf extract contains compounds terpenoid and flavonoid, and have antibacterial activity, MIC parkia speciosa leaf extract 2,5%, all gel formulation has antibacterial activity. The carbopol base gel has the most excellent antibacterial activity. All gel formulation is stable at a temperature of 25oC, less stable at a temperature of 0oC and 40oC . Conclusion: At 2.5% concentration, petai leaf extract already has antibacterial activity against Staphylococcus aureus bacteria.